2012
DOI: 10.1007/s00418-012-0950-3
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of the role of Pinin in the development of zebrafish posterior pharyngeal cartilages

Abstract: Pinin (pnn), a nuclear and desmosome-associated SR-like protein, has been shown to play multiple roles in cell adhesion, transcriptional regulation, pre-mRNA splicing and mRNA export. Because of the embryonic lethality of pnn-deficient mice, here we used the zebrafish system to investigate the functions of pnn. Injection of morpholinos into zebrafish to knockdown pnn resulted in several obvious defective phenotypes, such as short body, bent tail, and an abnormal pigment distribution pattern. Moreover, aberrant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Pnn is crucial for regulating neural crest proliferation and differentiation in zebrafish embryos. 59 Nucleolin (Ncl) involved in RNA binding modulates ribosomal RNA (rRNA) transcription and post-transcriptional regulation in zebrafish embryos. 60 Zc3h14 is a polyadenosine [poly(A)] RNA-binding protein and controls the proper length of poly(A) tails.…”
Section: Resultsmentioning
confidence: 99%
“…Pnn is crucial for regulating neural crest proliferation and differentiation in zebrafish embryos. 59 Nucleolin (Ncl) involved in RNA binding modulates ribosomal RNA (rRNA) transcription and post-transcriptional regulation in zebrafish embryos. 60 Zc3h14 is a polyadenosine [poly(A)] RNA-binding protein and controls the proper length of poly(A) tails.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that Pnn plays essential roles during embryogenesis [ 1 , 18 ], while the participation of Pnn in tumorigenesis and metastasis in certain types of cancers was also reported [ 6 , 19 , 20 , 21 , 22 ]. Although several studies have attempted to reveal the role of Pnn in primary astrocytes and corneal cells [ 16 , 23 , 24 ], the role and regulation of Pnn in non-dividing cells, particularly in neurons, remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the concurrence of skeletal defects, disorganized distribution of melanocytes and cardiac oedema has been observed in zebrafish with knockdown of the pinin ( pnn ) gene, which encodes a nuclear and desmosome-associated protein that modulates alternative splicing of a specific subset of target genes 30 .…”
Section: Discussionmentioning
confidence: 99%